Factors, influencing to the recruitment of international multicenter clinical trials of II-III phases - S. S. Milovanov (Izdatelstvo OKI, 2023)
Recruiting patients to a clinical trial is a process with many limitations. First of all, the time-limited and lengthening of the patient recruitment process in time increases the risk of failure of the entire study. In addition to the time factor, many other factors affect the recruitment of patients. The influence of factors is multidirectional and one factor can affect both positively and negatively the recruitment of patients. We have considered some of the factors within the framework of our proposed classification. Materials and methods. A retrospective analysis of 4 international multicenter clinical trials (MSCI) of phases II-III on the recruitment of patients, depending on the influence of factors, was carried out. The purpose of the study. To consider the influence of various factors on the set of patients by changing the set of patients and some other parameters and indicators. Statistical analysis. Descriptive statistics with typing. Results. The factors are classified into two groups and their influence on the recruitment of patients is considered. Discussion. According to the literature, the authors have developed a large number of classifications of groups, and we have proposed our own classification.